IM and SMS Reference Services for Libraries : (THE TECH SET® #19). - Bielskas, Amanda (Tech set, 2012)
Users want real-time answers to their reference questions wherever and whenever they are. Increasingly, that means SMS and IM services. Providing those is easier than you might think!